2012
DOI: 10.2214/ajr.11.6890
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Rate of Repeat Imaging: Import of Outside Images to PACS

Abstract: Importing outside images to PACS reduces the rate of repeat imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…In addition, searching for studies from other sources wastes provider time [9–12] and delays treatment [13]. Finally, imaging has high utility in the diagnosis and treatment of disease, but inaccessible studies cannot support clinical decision making [11,14]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, searching for studies from other sources wastes provider time [9–12] and delays treatment [13]. Finally, imaging has high utility in the diagnosis and treatment of disease, but inaccessible studies cannot support clinical decision making [11,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Several quantitative evaluations indicate that use of image sharing technologies reduces imaging utilization, particularly that for repeat and unnecessary imaging [14,2225]. However, other studies show inconsistent results, or no effect at all [2628].…”
Section: Introductionmentioning
confidence: 99%
“…24 We found that the type of practice women attend for mammography screening may influence their ability to readily access additional breast imaging required to complete diagnostic work-ups after abnormal screening. Specifically, women attending multi-specialty breast centers and full diagnostic radiology practices for screening are more likely to have advanced breast imaging services readily available compared to women attending non-radiology or breast imaging only practices.…”
Section: Discussionmentioning
confidence: 88%
“…Much of the interest in containing escalating imaging costs has focused on curbing overutilization by reducing inappropriate tests [2, 4, 1016]. In view of prior studies pointing to low likelihood of finding significant abnormality on imaging in uncomplicated headache [5, 9, 17, 18], both the American College of Radiology (ACR) and the American Association of Neurology have recommended limited use of neuroimaging in patients with headache [5, 6].…”
Section: Discussionmentioning
confidence: 99%